Hubungan antara Resiliensi dan Kelelahan pada Pasien Kanker yang Menjalani Kemoterapi: The Relationship Between Resilience and Fatigue Among Cancer Patients Undergoing Chemotherapy - rismawanti, Maylafasya; Cahyono, Hendra Dwi; Fatarona, Anita (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Cancer is a non-communicable disease that is the leading cause of death in the world, including Indonesia. One of the main treatments for cancer is chemotherapy, which although effective, often causes severe side effects, one of which is fatigue. Fatigue in cancer patients not only affects the physical, but also emotional and mental. In dealing with this condition, resilience plays an important role. Resilience can help patients survive, adapt, and stay enthusiastic about undergoing treatment. This study is a quantitative study with a cross-sectional approach, using The Connor-Davidson Resilience Scale (CD-RISC) questionnaire on the resilience variable and the Fatigue Assessment Scale (FAS) questionnaire on the Fatigue variable. The sampling technique is non-probability sampling by consecutive sampling. The number of samples is 132 respondents in cancer patients undergoing chemotherapy at Baladhika Husada Hospital, Jember. Data analysis uses univariate analysis with the Spearman rank. The results of the study showed that respondents who had poor resilience and severe fatigue were 15 (11.4%), moderate resilience and moderate fatigue were 41 (31.1%), and good resilience and mild fatigue were 33 (25%). The results of the Spearman rank test analysis obtained a p value of 0.000 <α (0.05) and the contingency value was equal to -0.465, meaning a moderate relationship with a negative correlation direction. There is a significant relationship between resilience and fatigue in cancer patients undergoing chemotherapy at Baladhika Husada Hospital, Jember.